Proposed Negative Statutory Instruments under the European Union (Withdrawal) Act 2018 : Includes 3 Recommendations ; Draft Aviation Safety (Amendment etc) (EU Exit) Regulations 2019 ; Building (Amendment) Regulations 2018 : 9th Report of Session 2017-19 /: Includes 3 Recommendations ; Draft Aviation Safety (Amendment etc) (EU Exit) Regulations 2019 ; Building (Amendment) Regulations 2018 : 9th Report of Session 2017-19. ([2018-12-12]) - Unknown
No abstract available